Rapid tests for sexually transmitted infections (STIs): the way forward. (6th December 2006) - Peeling, R W; Holmes, K K; Mabey, D; Ronald, A
Abstract : In the developing world, laboratory services for sexually transmitted infections (STIs) are either not available, or where limited services are available, patients may not be able to pay for or physically access those services. Despite the existence of national policy for antenatal screening to prevent congenital syphilis and substantial evidence that antenatal screening is cost-effective, implementation of syphilis screening programmes remains unacceptably low because of lack of screening tools that can be used in primary health care settings. The World Health Organization Sexually Transmitted Diseases Diagnostics Initiative (SDI) has developed the ASSURED criteria as a benchmark to decide if tests address disease control needs: A ffordable, S ensitive, S pecific, U ser-friendly, R apid and robust, E quipment-free and D eliverable to end-users. Rapid syphilis tests that can be used with whole blood approach the ASSURED criteria and can now be deployed in areas where no previous screening has been possible. Although rapid tests for chlamydia and gonorrhoea lack sensitivity, more tests are in development. The way forward for STI diagnostics requires a continuing quest for ASSURED tests, the development of a road map for test introduction, sustainable programmes for quality assurance, and the creation of a robust infrastructure linked to HIV prevention that ensures sustainability of STI control efforts that includes viral STIs.